Analisis Rantai Nilai Keripik Salak Pondoh Organik di Kelompok Tani Bangun Suruhan Desa Wonosroyo Kecamatan Watumalang Kabupaten Wonosobo Provinsi Jawa Tengah - Himmatul Miftah; Siti Masithoh; Arti Yoesdiarti; Namira Laila Ramadhani; Ikhsan Qodri Pramartaa; Tiara Amanda Lestari (Universitas Djuanda Bogor, 2022)
This study aims to determine the marketing channels in the Organic Snakefruit Pondoh Chips value chain in the Bangun Suruhan Farmer's Group, Wonosroyo Village, Watumalang District, Wonosobo Regency, to find out the profits obtained by selling organic Snakefruit Pondoh Chips, added value and margin. This research was conducted in March - May 2022. The data collection method was conducted by interview. Respondents in this study were 24 organic snakefruit farmers, 5 collector traders, 1 organic Snakefruit Pondoh Chips processor in Bangun Suruhan Farmers Group and 2 retailers. Data analysis used value chain analysis, R/C, farmer's share, R/C analysis on organic snakefruit pondoh farmers selling organic snakefruit pondoh to collector traders in bulk form obtaining an R/C value of 1.38 earning a profit of Rp. 2,297,311.39-, if organic snakefruit pondoh farmers sell organic snakefruit pondoh to collectors in the form of grades get an R/C value of 2.41 and a profit of Rp. 8,558,811.39-, the calculation of farmer's share obtained by organic snakefruit pondoh farmers in channel 1 is 30.0% and in channel II is 10.0%. Analysis of the added value of Organic Snakefruit Pondoh Chips in the Bangun Suruhan Poktan resulted. The value formed in the local market, including souvenir shops, earns a margin of Rp. 35.000,0-,resellers get a margin of Rp. 22.0000.0-, shopee earns a margin of Rp. 27,000,0-,